2021
DOI: 10.3389/fmed.2021.678157
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors for Weaning Failure of Mechanically Ventilated Patients With COVID-19: A Retrospective Study in National Medical Team Work

Abstract: Purpose: This study aimed to describe the clinical and laboratory characteristics and the parameters of the respiratory mechanics of mechanically ventilated patients with confirmed COVID-19 pneumonia and to clarify the risk or protective factors for weaning failure.Methods: Patients diagnosed with COVID-19 pneumonia were selected from the special intensive care unit (ICU) of the Sino-French New City Branch of Tong Ji Hospital, Wuhan, and treated by the National Medical Team Work. They were divided into success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Weaning failure results in longer duration of MV and longer ICU stay which both are associated with adverse outcome. Zhao et al, [ 40 ] reported also a significant association between the weaning outcome and the 28 th day mortality in SARS-CoV2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Weaning failure results in longer duration of MV and longer ICU stay which both are associated with adverse outcome. Zhao et al, [ 40 ] reported also a significant association between the weaning outcome and the 28 th day mortality in SARS-CoV2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a low PEEP strategy was found to be more beneficial for patients with sepsis weaning from ventilation. Although the low-level PEEP strategy did not have a significant effect on improving ventilator weaning in a cohort study ( 28 ), it still has the potential to promote ventilator weaning ( 29 ). There is increasing evidence that high levels of PEEP are a risk factor in reducing the likelihood of WS ( 19 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of the patient's preparedness for weaning is one of the important tasks that nurses perform in the ICU. Effective weaning features include better weaning preparation interventions, regular weaning readiness assessments, techniques to enhance and encourage spontaneous breathing during weaning, and the use of spontaneous breathing trials (SBT) to gauge the likelihood of weaning the patient from the ventilator [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged mechanical ventilation and the uncertainty surrounding weaning can lead to psychological distress, moreover patients experiencing high levels of stress or anxiety may require a longer time on the ventilator, leading to increased healthcare costs and potential complications associated with prolonged mechanical ventilation. The psychosocial predictors of ventilator weaning outcomes in patients have not been systematically evaluated [ 7 ].…”
Section: Introductionmentioning
confidence: 99%